2013
DOI: 10.4314/ejesm.v6i1.12
|View full text |Cite
|
Sign up to set email alerts
|

Effect of <i>Moringa oleifera</i> marinade on microbial stability of smoke-dried African Catfish (<i>Clarias gariepinus</i>)

Abstract: The study examined the antimicrobial effect of Moringa oleifera marinade on smoke-dried catfish stored at ambient temperature (37±2 0 C) for two months. The experimental treatments are the control, 1%, 2% and 3% (w/v) Moringa oleifera Marinade (MOM) and 5% Brine (w/v) solutions. Seventy-five fishes of average weight of 260±8g were gutted, washed and randomly assigned to the treatments. Thereafter, the fishes were soaked in the treatments for 2 hours and later hot smoked for 12hours. After smoking, the fishes w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 11 publications
(8 reference statements)
1
5
0
Order By: Relevance
“…Initial rise in TVC and TCC was observed which eventually decline in the population by the 15th day of storage for all samples. Similar observation was reported by Adeyemi, El‐Imam, Dosunmu, and Lawal (). M. oleifera leafmeal was used and according to Gbolagunte et al () this could be as a result of unfavorable condition resulting in rapid decline of microorganisms population due to the depletion of nutrients, accumulation of metabolic waste products, and other toxic materials in the fish flesh.…”
Section: Discussionsupporting
confidence: 91%
“…Initial rise in TVC and TCC was observed which eventually decline in the population by the 15th day of storage for all samples. Similar observation was reported by Adeyemi, El‐Imam, Dosunmu, and Lawal (). M. oleifera leafmeal was used and according to Gbolagunte et al () this could be as a result of unfavorable condition resulting in rapid decline of microorganisms population due to the depletion of nutrients, accumulation of metabolic waste products, and other toxic materials in the fish flesh.…”
Section: Discussionsupporting
confidence: 91%
“… (a) Flow chart of smoked fish production (Adeyemi et al., 2013 ; Adeyeye et al., 2015 ; Assogba et al., 2019 ; Dègnon et al., 2013 ; Goulas & Kontominas, 2005 ; Ubwa et al., 2015 ) and (b) smoked meat production (Poligné et al., 2001 ; Roseiro et al., 2011 ) …”
Section: Resultsmentioning
confidence: 99%
“…Flow chart of smoked fish production (Adeyemi et al, 2013;Adeyeye et al, 2015;Assogba et al, 2019;Dègnon et al, 2013;Goulas & Kontominas, 2005;Ubwa et al, 2015) and (b) smoked meat production (Poligné et al, 2001;Roseiro et al, 2011) Raw fish was achieved using gas chromatography coupled with mass spectrometry detection (Filho et al, 2003;Herrmann et al, 2014).…”
Section: Nitrosaminesmentioning
confidence: 99%
“…In this investigation, samples were examined for Salmonella, but no positive results were found. Likewise, [2] found that Salmonella was absent in all treated fish with M. oleifera. This could be as a result of the minced beef sample being maintained at the proper temperature and experiencing minimal sample movement [5].…”
Section: Discussionmentioning
confidence: 89%